Development of 6-amido-4-aminoisoindolyn-1,3-diones as p70S6K1 inhibitors and potential breast cancer therapeutics - Thornton, Adrian; Komati, Rajesh; Kim, Hogyoung; Myers, Jamiah; Petty, Kymmia; Sam, Rion; Johnson-Henderson, Elijah; Reese, Keshunna; Tran, Linh; Sridhar, Vaniyambadi; Williams, Christopher; Sridhar, Jayalakshmi (Frontiers in Molecular Biosciences, 2024)
IntroductionMany breast cancer therapeutics target the PI3K/AKT/mTOR oncogenic pathway. Development of resistance to the therapeutics targeting this pathway is a frequent occurrence. Therapeutics targeting p70S6K1, a downstream member of this pathway, have recently gained importance due to its critical role in all types of breast cancer and its status as a prognostic marker. We have developed a new class of p70S6K1 inhibitors that show growth inhibition of MCF7 breast cancer cells.MethodsA series of 6-amido-4-aminoisoindolyn-1,3-dione compounds was developed against p70S6K1 using docking, computational modeling tools, and synthesis of the designed compounds. The p70S6K1 inhibition potency of the compounds was investigated in an initial high-throughput screening followed by IC50 determination for the most active ones. The best compounds were subjected to proliferation assays on MCF7 breast cancer cells. The targeting of p70S6K1 by the compounds was confirmed by studying the phosphorylation status of downstream protein rpS6.ResultsIn this study, we have identified a new class of compounds as p70S6K1 inhibitors that function as growth inhibitors of MCF7 breast cancer cells. The structural features imparting p70S6K1 inhibition potency to the compounds have been mapped. Our studies indicate that substitutions on the phenacetyl group residing in the cleft A of the protein do not contribute to the inhibition potency. Three compounds (5b, 5d, and 5f) have been identified to have sub-micromolar inhibition potency for p70S6K1. These compounds also exhibited growth inhibition of MCF7 cells by 40%–60% in the presence of estradiol.